2015
DOI: 10.5935/1806-0013.20150062
|View full text |Cite
|
Sign up to set email alerts
|

Physiotherapeutic intervention on chronic lumbar pain impact in the elderly

Abstract: BACKGROUND AND OBJECTIVES:Geriatric population is considerably increasing. However, musculoskeletal disorders, especially chronic low back pain, which is one of the most common complaints during outpatient assistance, seem to grow together with this phenomenon and physiotherapy may be an alternative to treat such pathology. This study aimed at reviewing in the literature information about physiotherapeutic management for chronic low back pain in the elderly. CONTENTS: Twenty-six articles were selected by means… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
2
0
2
Order By: Relevance
“…Moreover, the appearance of diseases can also trigger depressive symptoms, due to, for example, the physical limitations and disability that they cause. 18 The presence of pain has shown a direct correlation with QLe is a frequent complaint among the elderly, 19 and can reach about 50% of the elderly in the community 20 and more than 70% in the institutionalized ones. 21 Its presence can impair mobility, the performance of daily tasks and make the individual more dependent on care, 10 thus compromising the QLe of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the appearance of diseases can also trigger depressive symptoms, due to, for example, the physical limitations and disability that they cause. 18 The presence of pain has shown a direct correlation with QLe is a frequent complaint among the elderly, 19 and can reach about 50% of the elderly in the community 20 and more than 70% in the institutionalized ones. 21 Its presence can impair mobility, the performance of daily tasks and make the individual more dependent on care, 10 thus compromising the QLe of the elderly.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the profile of the institutionalized elderly consisted predominantly of private residents of LTCF, women, long-lived, widows and with education from 1 to 8 years 12 and that are in agreement with other studies 11,17,18 . With the considerable increase in the number of elderly people in recent times, musculoskeletal disorders, especially chronic pain, have been one of the main complaints among this population 19 , and in up to 80% of cases, these symptoms persist for at least two years until the search for treatment 20 . Thus, chronic pain can be a compromising factor for dislocation and functional activities of daily living, implying disability and loss of QoL of the elderly 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo sobre a intervenção fisioterapêutica no impacto da dor lombar crônica em idosos, Jorge et al 15 , citam a dor lombar como uma das principais queixas entre os idosos. Os autores afirmam ainda que a dor está entre os principais fatores que limitam a possibilidade do idoso em manter seu cotidiano de maneira normal, prejudicando, de algum modo, a realização das atividades de vida diária bem como restringindo a convivência social.…”
Section: Métodounclassified